The godmother / Hannelore Cayre. - Cayre, Hannelore, 1963- (ECW Press, 2019)
Meet Patience Portefeux, 53, an underpaid Franco-Arab judicial interpreter for the Ministry of Justice who specialises in telephone tapping. Widowed after the sudden death of her husband, Patience is now wedged between university fees for her two grown-up daughters and nursing home costs for her ageing mother. She's laboured for 25 years to keep everyone's heads above water. Happening upon an especially revealing set of police wiretaps ahead of all other authorities, Patience makes a life-altering decision that sees her intervening in - and infiltrating - the machinations of a massive drug deal. She embarks on an entirely new career path: Patience becomes 'the Godmother.' This is not life in the French idyll of postcards and stock photos.